2007
DOI: 10.1523/jneurosci.4391-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase-9 Gene Knock-out Protects the Immature Brain after Cerebral Hypoxia–Ischemia

Abstract: Inhibition of matrix metalloproteinase-9 (MMP-9) protects the adult brain after cerebral ischemia. However, the role of MMP-9 in the immature brain after hypoxia-ischemia (HI) is unknown. We exposed MMP-9 (Ϫ/Ϫ) [MMP-9 knock-out (KO)] and wild-type (WT) mice to HI on postnatal day 9. HI was induced by unilateral ligation of the left carotid artery followed by hypoxia (10% O 2 ; 36°C). Gelatin zymography showed that MMP-9 activity was transiently increased at 24 h after HI in the ipsilateral hemisphere and MMP-9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
194
2
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(209 citation statements)
references
References 44 publications
10
194
2
3
Order By: Relevance
“…Excitotoxic and inflammatory processes are involved in both the early phase of brain ischemia and the regulation of MMP expression. However, one cannot rule out the possibility that the severity of tissue damage is a factor contributing to the increase in MMP-9 and TIMP-1 expression in HI mice, given that brain lesions are known to be more severe from a histological viewpoint in the HI model than in the excitotoxin models (7,18).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Excitotoxic and inflammatory processes are involved in both the early phase of brain ischemia and the regulation of MMP expression. However, one cannot rule out the possibility that the severity of tissue damage is a factor contributing to the increase in MMP-9 and TIMP-1 expression in HI mice, given that brain lesions are known to be more severe from a histological viewpoint in the HI model than in the excitotoxin models (7,18).…”
Section: Discussionmentioning
confidence: 99%
“…This balance between the two molecules is thought to reduce brain damage in HI events by protecting the blood-brain barrier (7). MMP inhibition provides neuroprotection against HI in the developing brain (21).…”
Section: Mmp-9/timp-1 In Perinatal Brain Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…29 On the other hand, MMP9 possesses a variety of nonmatrix substrates whose cleavage may protect from apoptosis. 8 Decreased apoptosis was observed in MMP9-deficient mice after partial hepatectomy 30 and cerebral hypoxia-ischemia, 31 although the underlying mechanisms were poorly understood. In contrast, we found that MMP9 was protective in acute kidney injury by markedly reducing apoptosis and thus accelerating renal function recovery.…”
Section: Discussionmentioning
confidence: 99%